Surviving the Impossibility of Black Motherhood: Trauma and Healing in Sherley Anne Williams’s Dessa Rose - Zsuzsanna Lénárt-Muszka ([sic])
The paper reads the novel Dessa Rose (1986) by African American author Sherley Anne Williams, and focuses on the duality of motherhood as compounding and healing trauma at the same time. After placing the novel is its socio-cultural and literary context, I argue, relying on Black feminist and Afro-pessimistic theory, that the subversive potential of Williams’s novel lies in its claim that enslaved Black women are capable of healing through (re-)appropriating what is meant to dehumanize them: their stories, their bodies, their children, and their communities.Keywords: contemporary African American literature, Black women’s literature, slavery, motherhood studiesThe novel Dessa Rose (1986) by African American author Sherley Anne Williams interrogates the consequences of the extreme humiliation and almost total annihilation and torture of the Black female body. The eponymous protagonist, an enslaved woman, is denied agency and narrative authority, and is dehumanized by several people in her environment – B ack and white, men and women alike. The text demonstrates how the simultaneous invisibility and hyper-visibility of Black women compounds the different types of trauma caused by slavery, such as being kept in bondage, the denial of bodily autonomy, an almost fatal escape, and giving birth under traumatic circumstances. In the following text, after placing the novel in its socio-cultural and literary context, I will anchor my analysis in Black feminist and Afro-pessimistic theory, and argue that the subversive potential of Williams’s novel lies in its claim that Black women are capable of healing through (re-)appropriating what is meant to dehumanize them: their stories, their bodies, their children, and their communities. In this process of wake work (Sharpe 16-19), the protagonist and her community create a new Black discourse of self-representation in defiance of the dominant, white supremacist discourse in order to construct, in Christina Sharpe’s words, “new ways to live in the wake of slavery, in slavery’s afterlives, to survive (and more) the afterlife of property” (18).